Processing the trauma of intrafamilial child sexual abuse. - Strachman Miller, Marjorie (Kansas State University, 2011)
While previous research has shown that some form of processing the trauma of IFCSA seems to occur for many IFCSA survivors, how the trauma of IFCSA is processed remains as a gap in the literature. In this exploratory study, I used qualitative methods to clarify what the nature of processing is and how it happens among IFCSA survivors. A phenomenological framework was utilized to understand the lived experience of processing IFCSA, which guided my main research question (What is the nature of how IFCSA is processed for some survivors?). Participants were recruited from the community via flyers, advertisements, and announcements. Seven eligible female participants completed two separate in-person semi-structured interviews. Participants also completed a timeline to organize their journeys in the first interview, and brought an object, or aesthetic representation, to represent their journeys of processing IFCSA in the second interview to triangulate data collection. To analyze the data, I used a constructivist grounded theory analysis approach. The general categories that emerged from the data in relation to processing IFCSA included the journey of processing IFCSA, the nature of processing IFCSA, and advice about processing IFCSA. The journey of processing included the individual journeys that each participant had been through. Participants described the nature of processing in terms of how they defined and experienced processing IFCSA experiences. For example, one participant’s definition of processing was the “uncomfortable process of really unpacking the implications of what actually happened. … acknowledging all the myriad ways that it’s actually affected you in your life. … And sort of personalizing what it is about that…has an affect on you.” Finally, advice from the participants for individuals, families, and helping professionals are described. Several participants recommended that victims seek help, as one participant discussed, “To me it’s not a stigma, a horrible thing, to go to counseling. That really it is for a healing, that it is another step of medically taking care of ourselves.” Clinical implications derived from this advice as well as from participants’ experiences processing IFCSA are discussed. Suggestions for future research to gain a better understanding about processing IFCSA are also discussed.
Keywords: Intrafamilial child sexual abuse; Processing trauma; Individual & Family Studies (0628)